PENGARUH LEVERAGE, LIKUIDITAS DAN UKURAN PERUSAHAAN TERHADAP PROFITABILITAS PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - yulita damayanti; Wulan Suryandani (Bisnis-Net, 2023)
Â Profitability is the skill of a company to create net income from activities that are tried throughout the accounting period made by management. The purpose of this research is to test and view the effect of leverage, liquidity and company size on profitability in food and beverage companies listed on the Indonesia Stock Exchange in 2015-2021. The total number of companies is 32 companies and only 11 companies are used as samples that meet the requirements. The sampling method is purposive sampling. Data collection methods by means of documentation. The data analysis method used is multiple linear regression analysis. The results showed that leverage has a significant negative effect on profitability, liquidity has a significant positive effect on profitability and company size has an insignificant positive effect on profitability. The coefficient of determination displays a value of 0.242. The results of this study show that leverage, liquidity, and company size are able to interpret profitability by 24.2%, whereas 75.8% is explained by other variables that are not examined in depth in this studyÂ Keywords: Leverage, Liquidity, Company Size and Profitability.Â